ANALISIS DAN SIMULASI EFISIENSI BOILERDENGAN KAPASITAS UAP 1450 KG PER JAM - Mathew Yerikho Manuel, (2023)
A device in the form of a closed vessel used to produce steam is called a boiler. Steam is generated inside the boiler by heating a vessel filled with water using coal as fuel. The combustion process with water or steam in a boiler is the efficiency of a boiler (steam boiler) which generally uses liquid fuel (residue or diesel), solid (coal), and gas. In research conducted using a type of sub-bituminous fuel in the form of coal. Analysis of boiler efficiency uses a direct method, where the efficiency value is obtained from the division between output/output (steam) with incoming heat/input (fuel). The calculation results are directly known boilers using coal fuel with actual data, namely the amount of steam produced 1375 kg/hour, steam pressure and steam temperature of 174 kPa and 445 ºC, the amount of coal use 226 kg/hour, feed water temperature 276 ºC, GCV coal 4675 kcal/kg, steam enthalpy 794 kcal / kg, and feed water enthalpy 266 kcal / kg so that the direct efficiency of 68.7% is obtained. In addition, the results of more air value of 58% and theoretical air value of 6.7 kg / kg-f are obtained so that the ideal efficient air requirement is used in boilers with a steam capacity of 1450 kg / hour in the combustion process of 3.953 kg / kg-f for each kilogram of coal. In the simulation results, the countour pressure and velocity efficiency of the boiler work well because combustion and fluid flow run well then the thermal countour boiler efficiency works poorly because it is caused by coal flow and small temperature. While on the residual iterations graph works well while on the velocity - magnitude graph the highest speed is reached and the temperature graph is reached the highest temperature.